2017
DOI: 10.1371/journal.pone.0180023
|View full text |Cite
|
Sign up to set email alerts
|

Extreme low dose of 5-fluorouracil reverses MDR in cancer by sensitizing cancer associated fibroblasts and down-regulating P-gp

Abstract: We conducted a prospective, meaningful study of extreme low dose of 5-fluorouracil (5FU) as a metronomic agent targeting cancer associated fibroblasts (CAFs) to reverse Multidrug resistance (MDR) by sensitizing cancer associated fibroblasts and down-regulating P-glycoprotein (P-gp). The combination of 5FU and Taxol inhibited resistant KB-8-5 tumor growth by 79% and H460/Tax-R tumor growth by 55%. The inhibition was significant for both tumor types compared with Taxol treatment alone (p<0.001 and p = 0.0067, re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 16 publications
2
22
0
Order By: Relevance
“…In addition, elevated expression and activity of P-gp have been reported to be associated with poor clinical outcomes among cancer patients [24]. Based on these findings, a rationale was formulated for modulation of P-gp activity as a therapeutic approach [25]. A large number of compounds including verapamil, cyclosporine A, curcuminoids, and curcumin was demonstrated to exert reversal effects on MDR.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, elevated expression and activity of P-gp have been reported to be associated with poor clinical outcomes among cancer patients [24]. Based on these findings, a rationale was formulated for modulation of P-gp activity as a therapeutic approach [25]. A large number of compounds including verapamil, cyclosporine A, curcuminoids, and curcumin was demonstrated to exert reversal effects on MDR.…”
Section: Discussionmentioning
confidence: 99%
“…The occurrence of cancer resistance is related to the abnormality of multiple genes and their products, including multidrug resistance gene 1 (MDR1), lung resistance-related protein (LRP), etc [36]. P-gp is an MDR1 gene expression product and is an ATP-dependent transporter that can transport intracellular chemotherapeutic drugs out of the cell, thereby reducing the e cacy of the drug and leading to the emergence of drug resistance [37]. This study found that pCDS-circBIRC6 inhibited P-gp and MRP1 protein expression, and si-circBIRC6 increased the resistance to adverse reactions of DDP.…”
Section: Discussionmentioning
confidence: 99%
“…This is due to the fact that at a very low dose, 5 can target TAFs and inhibit multidrug resistance protein (Pgp). 52 In addition to the direct use of chemodrugs, nanotechnology-based drugs can also inhibit TAFs and thus improve antitumor efficacy. For example, to promote the penetration of nanomedicines into tumors and block stromal support to cancer cells, novel tumor stromal-targeted nanoparticles (FH-SSL-NAV) were designed to eliminate TAFs.…”
Section: Therapeutic Strategies For Targeting Tafsmentioning
confidence: 99%
“…Studies have indicated that combination of paclitaxel with a low dose of 5-FU can effectively inhibit tumor growth hormone, and improve the effectiveness of chemotherapy. This is due to the fact that at a very low dose, 5-FU can target TAFs and inhibit multidrug resistance protein (P-gp) …”
Section: Therapeutic Strategies For Targeting Tafsmentioning
confidence: 99%